2019
DOI: 10.11606/1807-0205/2019.59.29
|View full text |Cite
|
Sign up to set email alerts
|

Diet of bromeliad-frog Phyllodytes luteolus (Anura, Hylidae) in Atlantic Forest environments: what have the frogs been eating outside sandy coastal plains?

Abstract: Knowledge about the diet of anurans in different environments is essential to understanding important aspects of their trophic ecology. The bromeliad-frog Phyllodytes luteolus inhabits tank bromeliads in sandy coastal plains and lowland forests on the mainland, as well as a continental island in southeastern Brazil. In this work, we describe and analyze the diet of P. luteolus in three environments. We obtained the consumed prey items of 92 frogs (32 from sandy coastal plain, 32 from lowland forest and 28 from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Studies comparing the diets of anuran populations in different localities have shown that specialist species tend to maintain their preferences for a specific prey category, regardless of their habitat (e.g. Mageski et al, 2019 – for Phyllodytes luteolus ). In contrast, generalist species exhibit variations in their diet as the environment changes, which is likely due to differences in prey availability across their habitats (García‐Padrón & Quevedo, 2022; Santana et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing the diets of anuran populations in different localities have shown that specialist species tend to maintain their preferences for a specific prey category, regardless of their habitat (e.g. Mageski et al, 2019 – for Phyllodytes luteolus ). In contrast, generalist species exhibit variations in their diet as the environment changes, which is likely due to differences in prey availability across their habitats (García‐Padrón & Quevedo, 2022; Santana et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…49, May 7, 2021). This alternative method has been applied in recent years to avoid unnecessary deaths of large numbers of animals RÖDDER, 2010;MAGESKI et al, 2019;OLIVEIRA-SOUZA et al, 2022). After these laboratory procedures, they were released close to sampling points.…”
Section: Samplingmentioning
confidence: 99%